2009
DOI: 10.1002/bjs.6429
|View full text |Cite
|
Sign up to set email alerts
|

Liver dysfunction and sepsis determine operative mortality after liver resection

Abstract: Sepsis plays a key role in the death of patients with liver dysfunction after hepatectomy. Early recognition and aggressive treatment of sepsis may reduce mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…However, the study population was heterogeneous, including patients with carcinoma of the biliary tract, benign liver tumors, and metastatic liver tumors. The present study, limited to patients with HCC arising from underlying liver disease, [44] 2009 LM, HCC 1271 Age, cirrhosis Rahman [45] 2008 LM, HCC 138 Resection of ≥5 Couinaud segments Mullen [19] 2007 LM, HCC, CCC 1059 b Age Associated major intraabdominal procedures e Cucchetti [34] 2006 HCC 154 a MELD score Schindl [13] 2005 LM, HCC 104 RLV, BMI Balzan [18] 2005 HCC, LM 775 Age, fibrosis stage Kubo [46] 2004 HCC 251…”
Section: Discussionmentioning
confidence: 99%
“…However, the study population was heterogeneous, including patients with carcinoma of the biliary tract, benign liver tumors, and metastatic liver tumors. The present study, limited to patients with HCC arising from underlying liver disease, [44] 2009 LM, HCC 1271 Age, cirrhosis Rahman [45] 2008 LM, HCC 138 Resection of ≥5 Couinaud segments Mullen [19] 2007 LM, HCC, CCC 1059 b Age Associated major intraabdominal procedures e Cucchetti [34] 2006 HCC 154 a MELD score Schindl [13] 2005 LM, HCC 104 RLV, BMI Balzan [18] 2005 HCC, LM 775 Age, fibrosis stage Kubo [46] 2004 HCC 251…”
Section: Discussionmentioning
confidence: 99%
“…1 Capussotti et al 2 demonstrated that the association of postoperative liver dysfunction and sepsis were the main determinants of in-hospital mortality rate after liver resection.…”
Section: Main Outcome Measuresmentioning
confidence: 99%
“…Posthepatectomy liver dysfunction or failure remains an extremely feared complication, still reported in up to 30% of the cases: In spite of major innovations in surgical and anesthesiological techniques and in the postoperative care, mortality remains high [27][28][29][30] . Postoperative liver dysfunction is more frequent in cirrhotic patients who underwent hepatic resection: According to the literature, major risk factors are inadequate preoperative assessment of liver functional reserve, too "aggressive" resection, perioperative hemorrhagic complications and transfusion needs, postoperative infective complications [30][31][32][33][34][35] . Usually (but not exclusively), indications and extension of resective surgery are tailored according to: (1) presence or absence of ascites and hepatic encephalopathy in the preoperative period; (2) results of conventional static liver function tests (AST/ALT, serum Bilirubin level); (3) imaging (magnetic resonance imaging/magnetic resonance imaging volumetric imaging to predict the remnant hepatic volume); and (4) CTP and MELD scoring systems [23,[33][34][35] .…”
Section: The Role Of Igc Clearance Kinetics In the Preoperative Assesmentioning
confidence: 99%